(3GSJNOGe HQfGeL GdchQJ dJfejI HYV egGQGJ GdJacjQ GdEHOGYj hGdJacjQ GdfGbO dOi YjfI ef eYdeGJ QjGV GdCWaGd HOhdI GdchjJ (B/ s - (3CSeGA ajUd Ydj MeGOjs; (3NGdO YHOGdQGRb GdfLGQ (B: s ((3GdbGgQI (B: s (3CSeGA ajUd Ydj MeGOj (B: s, 2017)
(3gOaJ GdOQGSI Gdi GdJMbb ef aGYdjI HQfGeL GdchQJ dJdje GdJacjQ ai JfejI GdJacjQ GdGHOGYi h GdJacjQ GdfGbO dOi YjfI ef eYdeGJ QjGV GdCWaGd HOhdI GdchjJ(B: (3h JchfJ YjfI GdOQGSI ef (B10 (3eYdeGJ ef GdeDgdGJ h GdeJNUUGJ ai QjGV GdCWaGd h GSJNOeJ GdHGMKI ebjGS SJGfahQO jfjI GdUhQI GdQGHYI h ebjGS GdJacjQ GdGHOGYi HGSJNOGe GdGTcGd h ebjGS GdJacjQ GdfGbO GYOGO fgi GdRjGJ (B2016 (3h GNjQG HQfGeL GdchQJ dJYdje GdJacjQ(B: (3h GTGQJ fJGFL GdOQGSI Gdi hLhO aQhb OGdI GMUGFjG Hjf GdbjGS GdbHdi h GdbjGS GdHYOi HYO JWHjb HQfGeL GdchQJ dJYdje GdJacjQ h Pdc HGdfSHI ddJacjQ GdGHOGYi h GdJacjQ GdfGbO dOi eYdeGJ QjGV GdGWaGd HOhdI GdchjJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdfaSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJacjQ GdGHOGYis; (3HQfGeL GdchQJ s; (3JYdje GdJacjQ s